Leukemia escape in immune desert: intraocular relapse of pediatric pro-B-ALL during systemic control by CD19-CAR T cells. Issue 2 (16th September 2020) - Willier, Semjon; Raedler, Johannes; Blaeschke, Franziska; Stenger, Dana; Pazos Escudero, Montserrat; Jurgeleit, Florian; Grünewald, Thomas G P; Binder, Vera; Schmid, Irene; Albert, Michael H; Wolf, Armin; Feuchtinger, Tobias
Abstract : Background: Relapsed/refractory B-precursor acute lymphoblastic leukemia (BCP-ALL) remains a major therapeutic challenge in pediatric hematology. Chimeric antigen receptor (CAR) T cells targeting CD19 have shown remarkable initial response rates in BCP-ALL patients, while long-term leukemia control rate is only about 50%. So far, main mechanisms of BCP-ALL relapse after CD19-CAR T-cell therapy have been either insufficient CAR T-cell persistence in vivo or loss of surface CD19. Case Report: Here, we report an exceptional presentation of BCP-ALL relapse in the eye during the systemic control through CAR T-cell therapy. We report a case of fatal intraocular relapse in a pediatric patient with pro-B-ALL after initial response to CD19-CAR T-cell therapy. One month after CD19-CAR T-cell therapy, remission was documented by bone marrow aspirate analysis with absence of CD19 + cells and CD19-CAR T cells could be detected in both peripheral blood and bone marrow. At the same time, however, the patient presented with progressive visual disturbance and CD19 + cells were found within the anterior chamber of the eye. Despite local and systemic therapy, ocular relapse led to BCP-ALL dissemination and systemic relapse within weeks. The eye represents a rare site for local manifestation of BCP-ALL, but isolated intraocular relapse is a clinically unreckoned presentation of BCP-ALL in the era of CD19-CAR T cells. Conclusion: During systemic control of BCP-ALL through CD19-CAR T cells, relapse can emerge in the eye as an immune-privileged organ. Ocular symptoms after CD19-CAR T-cell therapy should guide the clinician to elucidate the etiology in a timely fashion in order to adjust leukemia treatment strategy. Both, local immune escape as well as insufficient CAR T-cell persistence may have contributed to relapse in the reported patient. Mechanisms of relapse in an immune desert under CAR T-cell therapy require future clinical and experimental attention. In particular, ocular symptoms after CAR T-cell therapy should be considered a potentially early sign of leukemia relapse.